RIGHT MEDICATION RELATED TO DRUG CENTRALIZED IN RSUD SIDOARJO - Aprilia Aprilia; Nursalam Nursalam; Candra Panji Asmoro (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Introduction. Centralized drug is a management of the entire drug which is entirely done by nurses to administration to patients. Right medication is the process of right drug administration which is done by nurses based on 6 rights of medication, and wary of side effects. The purpose of this study was to analyze the corelation between centralized drug, team leadership, and nurse`s knowledge with right medication among nurses. Methods.The design of the study was descriptive corelational with cross-sectional approach. The population was inpatient nurses in RSUD Sidoarjo. Total sample was 114 respondents was selected by purposive sampling. The independent variables in this study: centralized drug, team leadership, and nurse`s knowledge. The dependent variable was right medication. Data were collected by using questionnares for independent variables and dependent variable. Data were analyzed by using Binary Logistic Regression with degree of significance α>0,05. Results. Binary Logistic Regression test showed non significance level between centralized drug with right medication (P=0.501), team leadership with right medication (P=0.874), and nurses`s knowledge with right medication (P=0.243). Discussion. This study concluded centralized drug, team leadership, and nurse`s knowledge were good. But, there are nurses that have negative value at right medication, however right medication in RSUD Sidoarjo has majority positive value. Keywords: centralized drug, right medication